2006
DOI: 10.1111/j.1365-2907.2006.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Gray whaleEschrichtius robustuspopulation and stock identity

Abstract: 1. In response to conservation and management concerns about gray whale Eschrichtius robustus population and stock structure, we provide an overview of the life history and ecology of gray whales as a context for discussion of population and stock structure within the species. Historically eastern and western North Pacific gray whales were managed separately because: (i) their ranges do not overlap; (ii) genetic analyses indicate that the two populations are significantly different; and (iii) eastern gray whal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 60 publications
2
53
0
Order By: Relevance
“…Very few data are currently available on historical abundance and whaling effort in the western Pacific stock (20), but it is possible that this population was substantially larger than it is now. Future analysis of these two populations using multiple nuclear loci and the IM approach used by Won and Hey (25) to investigate ancestral and effective sizes in chimpanzees might be a profitable way to address these issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few data are currently available on historical abundance and whaling effort in the western Pacific stock (20), but it is possible that this population was substantially larger than it is now. Future analysis of these two populations using multiple nuclear loci and the IM approach used by Won and Hey (25) to investigate ancestral and effective sizes in chimpanzees might be a profitable way to address these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Available data show no observable structure within the eastern Pacific gray whale population (reviewed in ref. 20). To further confirm this result, we collected data from six microsatellite loci for the same whales used in this study and estimated the probabilities of one population (K ϭ 1) versus multiple populations (K Ͼ 1) by using STRUCTURE, version 2 (21).…”
Section: Materials and Methods)mentioning
confidence: 99%
“…Samples from individual gray whales were taken between 1991 and 2004 from the eastern North Pacific population via biopsy and necropsy sampling (see LeDuc et al 2002, for additional sampling information), which is thought to be panmictic (Swartz et al 2006). DNA extraction of seven additional eastern North Pacific gray whale muscle and blubber tissues was performed using a QIAamp kit (QIAGEN, Valencia, CA).…”
Section: Obtaining Dna Sequence Datamentioning
confidence: 99%
“…Humpback whales show extensive population structure across and sometimes within ocean basins (Baker et al 1993). No strong genetic differentiation has been found within eastern Pacific gray whales (Swartz et al 2006), though the lack of strong structure might reflect whaling history (Alter et al 2008). Population structure within Antarctic minke whales is largely unknown, but recent studies have indicated some differentiation between whales in the Pacific and those in the Indian Ocean sectors of Antarctic waters (Pastene 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Broadscale seasonal migratory patterns of many of the large whale species have been described (e.g. Calambokidis et al 2000, Swartz et al 2006, Barlow et al 2011, and although pronounced seasonal distribution shifts of small cetaceans have been identified (Dohl et al 1986, Green et al 1992, 1993, Forney & Barlow 1998, they are typically not as well understood and may vary considerably from year to year.…”
Section: Introductionmentioning
confidence: 99%